KAJIAN POLA KETERKAITAN FUNGSIONAL JAWA TENGAH-DAERAH ISTIMEWA YOGYAKARTA - Mursid Zuhri (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2002)
The Purpose of this research to identify on correlation between regionon boundary area in the Central Java and DIY which limit each other that focused on subdistrict in boundary area. To reach this goal, we have toi dentify :a) potential of socio-economic on each area, b) the problems in each area, c) functional correlation between areas, d) the element to form correlation functional. The result of this research show that no correlation functional happen in the mostboundary areas between the Central Java and DIY. The element that cause no functional correlation are limit by homogen charateristic on the hill and most boundary area. Correlation functional only happen, between I) Subdistrict Tempel (Slernan) with Subdistrict Salam, Subdistrict Ngluwar, Sub district Srumbung, 2) Sub district Cangkringan (Slcman) with Sub district Kemalang (Klaten). 4) Sub district Pracimantoro (Wonogiri) with Sub district Rongkop (Gunungkidul. Element to form correlation functional between the areas are: trading activities, industry. education, socio-culture.